Influence of thermo-mechanical history on the ordering kinetics in 18 carat Au alloys. (1st June 2020) - Garcia-Gonzalez, Marina; Van Petegem, Steven; Baluc, Nadine; Dupraz, Maxime; Honkimaki, Veijo; Lalire, Fanny; Van Swygenhoven, Helena
Abstract: Precious alloys are subjected to a series of mechanical and thermal operations during manufacturing. For 18 carat gold alloys the processing operations can induce L10 ordered nanodomains, known to lead to the build-up of residual stresses, which are the prime cause for shape distortion. Here, in situ high-energy synchrotron X-ray diffraction experiments in combination with electron microscopy observations reveal the influence of the thermo-mechanical history and chemical composition on the ordering kinetics during isochronal heating. Initially, during heating, the elastic lattice strain in the ordered nanodomains increases. The ordering rate and accumulation of lattice strain depend on the cooling rate, predeformation and chemical composition. Above a given temperature, which depends on the deformation state and chemical composition, the lattice strain in the ordered domains relaxes which is ascribed to the formation of a tweed structure. Graphical abstract: Image, graphical abstract